2002
DOI: 10.1515/znc-2002-7-812
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antimicrobial Activity of Essential Oil and HexaneÐEther Extract of Tanacetum santolinoides (DC.) Feinbr. and Fertig

Abstract: The essential oil of the aerial parts of Tanacetum santolinoides was analyzed by capillary GLC and GLC-MS. Altogether 30 components were identified. The main constituents were thymol (18%), trans-thujone (17.5%), trans-chrysanthenyl acetate (13.2%), cis-chrysanthenyl acetate (9.2%), umbellulone (9.7%) and 1,8-cineole (4.7%). Similar essential oil pattern in addition to palmitic acid methyl ester, palmitic acid, stigmasterol, sitosterol and two flavonoidal aglycons were found in the n-hexane-ether extract. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 1 publication
2
24
1
Order By: Relevance
“…As can be seen from Table 1, the essential oil is composed mainly of monoterpene hydrocarbons (87.9%), followed by oxygenated monoterpenes (4.1%) and oxygenated sesquiterpenes (7.8%). Compared to other Tanacetum species [2][3][4][5][6][7][8][9]11], in this study we found considerable qualitative and quantitative differences in the essential oil composition of Tanacetum sample collected from Ilic. This may be due to genotypic variation and climatic and environmental factors [7].…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…As can be seen from Table 1, the essential oil is composed mainly of monoterpene hydrocarbons (87.9%), followed by oxygenated monoterpenes (4.1%) and oxygenated sesquiterpenes (7.8%). Compared to other Tanacetum species [2][3][4][5][6][7][8][9]11], in this study we found considerable qualitative and quantitative differences in the essential oil composition of Tanacetum sample collected from Ilic. This may be due to genotypic variation and climatic and environmental factors [7].…”
contrasting
confidence: 46%
“…In the past, many studies have reported on the essential oil compositions of various Tanacetum species. In the previous studies [2][3][4][5][6][7][8][9][10][11][12], camphor, 1.8-cineole, α-thujone, carvone, thymol, trans-sabinyl acetate, borneol, caryophyllone oxide, (E)-myroxide, sabinene, bornylacetate, and isopulegone were determined as the major constitutents of the essential oils of Tanacetum species. The findings show that the genus Tanacetum had a considerable variation in essential oil composition.…”
mentioning
confidence: 99%
“…According to recent studies, essential oils and extracts of Tanacetum genus exhibit anti-inflammatory (Brown et al, 1997;Ghantous et al, 2013;Mordujovich-Buschiazzo et al, 1996;Park et al, 2011;Sur et al, 2009), anticancer (Ghantous et al, 2013), antibacterial (Habibi et al, 2009;Hethelyi et al, 1991;Holopainen and Kauppinen, 1989;Mohsenzadeh et al, 2011), antiviral (Onozato et al, 2009), antifungal (Hethelyi et al, 1991), antihelmintic (Godinho et al, 2014), insecticidal (Hough-Golstein and Hahn, 1992;Nottingham et al, 1991;Panasiuk, 1984;Schearer, 1984;Suomi et al, 1986) and antiprotozoal effects (Izumi et al, 2008;Tiuman et al, 2005). Many studies have been reported on the essential oil composition of various Tanacetum species (El-Shazly et al, 2002;Goren et al, 2001;Greche et al, 2000;Judzentiene and Mockute, 2005;Kandemir et al, 2008;MajedJabari et al, 2002;Marongiu et al, 2009;Mockute and Judzentiene, 2004;Monfared et al, 2002;Piras et al, 2014;Polatoglu et al, 2011;Rohloff et al, 2004;Weyerstahl et al, 1999) and camphor, 1,8-cineole, ␣-thujone, carvone, thymol, trans-sabinyl acetate, borneol, caryophyllene oxide, (E)-myroxide, sabinene, bornyl acetate, isopulegone and artemisia ketone were identified as the major constituents. This genus is also found to contain sesquiterpene lactones (Aljancic et al, 2001;…”
Section: Introductionmentioning
confidence: 99%
“…Thujone has been found to be primary constituent of essential oils of several plants such as, Artemisia incana (Mojarrab et al, 2013), Artemisia deserti, Artemisia oliveriana (Rustaiyan et al, 2000), Artemisia kermanensis (Ganjali and Pourramezani Harati, 2012), Artemisia vulgaris (Govindaraj and RanjithaKumari, 2013), Commiphora tenuis (Asres et al, 1998), Croton urucurana (Simionatto et al, 2007), Mentha nativa (Bascope and Sterner, 2010), Mentha longifolia, Rosmarinus officinalis (Mohkami et al, 2014), Salvia fruticosa (Topcu et al, 2013), Salvia officinalis (Miladinovic and Miladinovic, 2000;Hadri et al, 2010;Monakhova et al, 2011;Darwish et al, 2013;Baj et al, 2013), Tanacetum santolinoides (Shazly et al, 2002), Tanacetum vulgare (Acha de la Cruz et al, 2008), Tripleurospermum caucasicum (Farjam et al, 2012) and Thuja occidentalis (Albert-Puleo, 1978).…”
Section: Characterization Of Isolated Larvicidal Compoundmentioning
confidence: 99%